Incidencia de fugas en la red de abastecimiento de agua potable de la ciudad Guaranda - Ulloa Ocaña, Bryan Antonio (2024)
Potable water leaks in supply networks, being difficult to locate, lead to water wastage and reduce the network's efficiency. When this problem occurs, the companies responsible for providing the service suffer significant financial consequences. Therefore, the present study aims to determine the incidence of leaks in the potable water supply networks of the city of Guaranda, to verify the reasons why uncontrolled water volume causes high economic losses. For this research, a methodology with a qualitative and quantitative approach was used; qualitative to understand the characteristics of the leaks and repair processes through on-site inspection, and quantitative with data processing on injected and billed volumes for the realization of the general water balance proposed by Cabrera et al. (1999), where uncontrolled flows ranging from 250.91 [l/s] to 585.50 [l/s] were obtained; percentages of uncontrolled water index proposed by the Water Regulation and Control Agency (2021), with an average of 40.15%, placing it in a "II-Medium" performance range and below the national average of 48.35%. According to the overall system performance proposed by Cabrera et al. (1999), a rating of "Poor" was obtained; economic losses amount to $846,730.50 [USD/year] due to uncontrolled flow, with a total loss of $748,863.06 [USD/year] from leaked uncontrolled flow, these being the highest values in the analysis period. Based on all these research results, various solutions are proposed to benefit the entity responsible for providing potable water.